An Assessment of the Levels of Anxiety and Depression in Patients with Recurrent Aphthous Stomatitis - Nagihan Bilal; M Fatih Karakus; Mihriban Dalkiran Varkal; Osman Fatih Boztepe; Bora Bilal; Selman Sarıca (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2016)
Backgrounds: There is a lack of valid and reliable studies in literature on both the distinctive and ambiguous relationship between the psychological profile and the occurrence of recurrent aphthous ulcers in the individual.  Objectives: The etiology of recurrent aphthous ulceration (RAU) is not well understood. This study analyzes the psychological treatment of patients with recurrent aphthous using valid, confidential and effective psychological measures.  Materials: In this study we included 50 patients with recurrent aphthous stomatitis who were undergoing no psychiatric treatment, as well as 50 age and gender matched healthy individuals as the control group. The study utilized the Beck Depression Inventory and STAI-S and STAI-T tests, which have been evaluated as valid sources for assessment.  Results: A comparison of the aphthous ulcer group with the control group revealed no significant difference in STAI-S psychiatric scores (p>0.05). In contrast, the scores of the STAI-T of the patients with aphthous ulcers were found to be increased when compared to the control group (p<0.05).  Conclusion: This study proposes a different overview for this area of etiologic research on this disease, based on the significant differences revealed by the STAI-T, which discovered increased anxiety levels in patients. Accordingly, there is need for more investigation into comorbid anxiety disorder and depression in patients with recurrent aphthous stomatitis, and an assessment of treatment with psychological traits, implying that further comparative studies are required to understand the issue.